Prevention and management of osteoporosis and osteoporotic fractures in persons with a spinal cord injury or disorder: A systematic scoping review. (2nd November 2019) - Zleik, Nour; Weaver, Frances; Harmon, Robert L.; Le, Brian; Radhakrishnan, Reshmitha; Jirau-Rosaly, Wanda D.; Craven, B. Catharine; Raiford, Mattie; Hill, Jennifer N.; Etingen, Bella; Guihan, Marylou; Heggeness, Michael H.; et al.
Abstract : Objectives: The primary objective was to review the literature regarding methodologies to assess fracture risk, to prevent and treat osteoporosis and to manage osteoporotic fractures in SCI/D. Study Design: Scoping review. Settings/Participants: Human adult subjects with a SCI/D. Outcome measures: Strategies to identify persons with SCI/D at risk for osteoporotic fractures, nonpharmacological and pharmacological therapies for osteoporosis and management of appendicular fractures. Results: 226 articles were included in the scoping review. Risk of osteoporotic fractures in SCI is predicted by a combination of DXA-defined low BMD plus clinical and demographic characteristics. Screening for secondary causes of osteoporosis, in particular hyperparathyroidism, hyperthyroidism, vitamin D insufficiency and hypogonadism, should be considered. Current antiresorptive therapies for treatment of osteoporosis have limited efficacy. Use of surgery to treat fractures has increased and outcomes are good and comparable to conservative treatment in most cases. A common adverse event following fracture was delayed healing. Conclusions: Most of the research in this area is limited by small sample sizes, weak study designs, and significant variation in populations studied. Future research needs to address cohort definition and study design issues.